Same as ever : Timeless Lessons on Risk, Opportunity and Living a Good Life - Housel, Morgan (Faridabad: Harriman House Ltd., 2023)
When planning for the future we often ask, (3z(BWhat will the economy be doing this time next year?(3y (BOr, (3z(BWhat will be different ten years from now?(3y (BBut forecasting is hard. The important events that will shape the future are inherently unpredictable. Instead, we should be asking a different question: What will be the same ten years from now? What will be the same one hundred years from now? Knowledge of the things that never change is more useful, and more important, than an uncertain prediction of an unknowable future. In Same As Ever, bestselling author Morgan Housel shares 24 short stories about the ways that life, behaviour, and business will always be the same. Armed with this knowledge of the unchanging, you will have a powerful new ability to think about risk, opportunity, and how to navigate the uncertainty of the future. As you see familiar themes repeat again and again in the years ahead, you$1 (Bll find yourself nodding and saying, (3z(BYep, same as ever.(3ys
Keywords: Human behavior -- Economics$1 (BPsychological aspectss; Decision making -- Social change -- Success